High mortality in geese associated with feeding tofu skin waste in Hebei Province, China - Xinwei Wang; Chang Cai; Yin Li; Hao Tang; Ian D Robertson (International Journal of Veterinary Science and Research - Peertechz Publications, 2020)
This case describes an unusual mortality in a flock of 4000 125-day-age geese fed with Tofu skin waste containing rongalite in a rural farm. Clinical symptoms, necropsy changes and intervention measures taken suggested poisoning of geese. Clinical investigation further confirmed that feeding Tofu skin waste was risk cause. This report is the first investigated case of feeding Tofu skin waste containing rongalite to lead gooses to dead to date, having ruled out acutely contagious diseases with highly pathogenic avian influenza, gosling plague, goose paramyxovirus infection, and avian cholera, as well as poisoning due to the use of insecticide, anticoagulant rodenticides and heavy metals.